Conservation Genomics for Threatened New Zealand Gentianella calcis (Gentianaceae) and Implications for Vulnerable Limestone Ecosystems - Robb W. Eastman‐Densem; David S. Glenny; Peter B. Heenan; Jana R. Wold; Pieter B. Pelser (Ecology and Evolution)
ABSTRACT In New Zealand, limestone habitats are a naturally insular ecosystem, and obligate limestone taxa are extremely vulnerable to habitat degradation and destruction. Many New Zealand endemic vascular plants obligate to limestone habitats are in urgent need of conservation management, but often there is a lack of knowledge to inform such actions. We used genotyping‐by‐sequencing to explore patterns of genetic diversity and connectivity in Gentianella calcis, a threatened limestone gentian with four subspecies that are endemic to the eastern part of the South Island. We show that these subspecies and their populations are strongly genetically differentiated and have limited genetic connectivity. Two main genetic groups were identified. One of these comprises G. calcis subsp. waipara (North Canterbury) and the other consists of G. calcis subsp. calcis, G. calcis subsp. manahune and G. calcis subsp. taiko (South Canterbury and North Otago). Although evidence of Isolation‐By‐Distance suggests that the strong population differentiation is a result of restricted gene flow among populations, potential signatures of local adaptation were also seen. Observed heterozygosity showed some variation between sampled populations, with this possibly reflecting differences in population histories as well as the effects of paralogy in some SNPs. Overall, our data suggest that conservation of all extant populations is needed to effectively conserve genetic diversity in G. calcis. However, because of resourcing limitations, the conservation of some populations may need to be prioritised over that of others.